OBSERVACIONES PALEOPATOLÓGICAS A LA TESIS DE BACHILLER DE JULIO C. TELLO - Altamirano Enciso, Alfredo (2013)
In 1908, Tello was 28 years old defended his bachelor thesis entitled Antiquity of syphilis in Peru at San Marcos University, Lima (Peru), showing the autochthonous of treponematosis. But at that time, the dominant theory of Peruvian physician was that syphilis arrived with the Spaniards during the contact period. His thesis is a pioneer interdisciplinary work meeting paleopathology, archaeology, etnohistory, physician and anthropology. He recovered fifteen thousands skulls from the highland of Lima, Huarochiri and Yauyos, and observed severe lesions of skull with perforation and gummatous borders with reaction periosteal. 16 skulls with this kind of lesion, burned, cremation, and depression created some confusion about the period and archaeological context not were good described. Nonetheless great archaeological remains like chaukallas and chukllas (two kind of stone structure of burials) can be indicator the density demographic human occurred at those places during the Late Intermediate Period (1200-1460 a.C.). Actual polemic discussion about the origin of treponematosis in South America few refer to great and pioneer Tello´s contribution.